The categorisation of resistance: interpreting failure to follow a proposed line of action in the diagnosis of autism amongst young adults - Hollin, Gregory; Pilnick, Alison (Blackwell Publishing, 2018)
sessions and ask how diagnosticians distinguish between interactional resistance as, on the one hand, a diagnostic indicator and, on the other, as a reasonable choice from a range of possible responses. We find evidence of various forms of resistance during ADOS sessions, but it is a resistance to a line of conversational action that is often determined to be indicative of autism. However, and as we show, this attribution of resistance can be ambiguous. We conclude by arguing for reflexive practice during any diagnosis where talk is the problem, and for a commitment to acknowledge the potential impact of diagnostic procedures themselves upon results.